PEMERIKSAAN ANGKA KUMAN DAN JAMUR SERTA IDENTIFIKASINYA PADA JAMU GENDONG BERAS KENCUR DAN TEMU LAWAK (Curcuma xanthorhiza Roxb.) DI KABUPATEN SEMARANG BAGIAN SELATAN - maulita cut nuria; dedeh ratna dewi; septaningsih septaningsih; sumantri sumantri (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2008)
ABSTRACTTradisional herbs made from natural ingredients containing many organic elements as the material feed for microbe that caused self decompose during storage. On the previously result of research did by Subhan Ratnawati (2002) shows there were many bacteria, including pathogen bacteria on galian singset herbal tonic carried in Jogjakarta city. The purpose study was intended to find out quantities and identified of bacteria and fungus present in the herbal tonic at ten regions in southern Semarang District. This study was conducted using 52 samples of „beras kencur and temulawak herbs‟ sold in Southern Semarang District. ALT method was used on this experiment and the medium used for growing in an aerobic manner was PCA (Plate Count Agar), while that used for growing in an anaerobic condition were TSA (Tripticase Soya Agar) and was incubated at 37oC for 24 hours. The media used for fungi were PDA (Potato Dextrose Agar). We used a 100-times amplifying microscope for identifying the fungi. The analysis on the data were conducted by calculating the numbers of bacteria and fungi for each sample and by identifying the bacteria and fungi present in the herbs. These numbers then compared to the prerequisites contained in the Indonesian Health Office (MENKES RI) No. 661/MENKES/SK/VII/1994. The analysis showed that the average number of bacteria in the sample of „beras kencur and temulawak herbs‟ that grown at the aerobic media was 4.7x105 CFU/ml and 3.1x104 CFU/ml, but we found no bacteria in the sample grown in an anaerobic manner. The numbers of bacteria grown in the aerobic manner exceeded the upper limits for bacteria number 104 (10000 CFU/ml). The average number of fungi from all samples was 50.7 CFU/ml and 40.5 CFU/ml, which was below the standard of 103 (1000 CFU/ml). The aerobic bacteria found in this study were Pseudomonas aeruginosa and Eschericia coli while the fungi found were Rhizopus, Aspergillus niger, Moniliaceae and Penisillium. Nearly all samples that examined in this study did not meet the conditions stipulated by Indonesian Health Office (MENKES RI) Number 661/MENKES/SK/VII/1994. Keywords: Herbal tonic carried, Bacteria Number and Fungi Number